COMPUTATIONAL MODEL OF THE AVIATION DIESEL ENGINE FOR HIL TESTING (Perner's Contacts, 2018)
This article deals with the development of a computational diesel engine model for the aerospace industry and HIL testing. The model is assembled from the blocks of own libraries in the Simulink software. To verify functionality, it was implemented on hardware for HIL testing, and responses to inputs generated by a simple real-time control algorithm were monitored. The aim was to verify and optimize the computational model for subsequent HIL testing with the prototype ECU.